An Investigation into the Stephens–Castro Synthesis of Dehydrotriaryl[12]annulenes: Factors Influencing the Cyclotrimerization. Issue 40 (18th October 2019) - Baxter, Paul N. W.; Al Ouahabi, Abdelaziz; Karmazin, Lydia; Varnek, Alexandre; Strub, Jean‐Marc; Cianferani, Sarah
Abstract : Detailed investigation into the CuX/base/phosphine modified Stephens–Castro syntheses of dehydrotriaryl[12]annulenes 1 –3 have shown that cyclization is suppressed by excess CuX, strong donor ligands, high dilution conditions, and thermally unstable ethynylcuprate monomers. Surprisingly, intermediate dimer 16 plays only a minor role in the formation of 2 and 4 . Overall, our findings are consistent with a cyclization pathway governed more by the nature of prior self‐association of the ethynylcuprate monomers. Crystallographic characterization of tetrameric by‐product 4, is also reported and revealed that it assembles into tubular stacks in the solid state. Abstract : An exploration of the reaction conditions under which the Stephens–Castro reaction of o ‐iodoarylethynylcuprates 6 and 8 preferentially afford macrocyclic dehydrotriaryl[12]annulenes 1 and 2 rather than giving polymeric products, suggest a mechanism that involves initial assembly of the ethynylcuprates into a soluble oligonuclear structure preorganized for cyclotrimerization.